PREDICTING YOUNG CONSUMER’S GREEN PURCHASE BEHAVIOR WITH GENDER AS MODERATING VARIABLE - ATIKAH MARWA, PUTRI ATIKAH MARWA B1024151007 (Jurnal Manajemen Update, 2019)
AbstractThe purpose of this research is to help the business to have better understanding about the trend of green purchasing in Pontianak. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. For the conceptual framework for this research was adopted by Yatish Joshi and Zillur Rahman (2015) with the additional of gender toward green purchase moderating variables. In order to assess the relationships between variables, a questionnaire-based approach was applied specifically designed for this study utilizing convenient sampling technique. Responses were randomly drawn as much as 100 respondents and for the location we choose Pontianak City. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software.Keywords: social influence, attitude toward green purchasing, perceived environmental knowledge,recycling  participation, eco-labeling, exposure to environmental message through the media,green purchasing.REFERENCESAllport, G. W. (1935). Attitudes. In a handbook of social psychology. Worcester, MA: Clark University Press.Amyx, D. A., DeJong, P. F., Lin, C. G., & Wiener, J. L. (1994). Influencers of Purchase Intentions for Ecologically Safe Products: an Exploratory Study''. AMA Winter Educators' Conference Proceedings, American Marketing Association, 341-7.Armstrong, G., & Kotler, P. (2005). Marketing: An Introduction. 7th Edition. Upper Saddle River: Prentice Hall.Babbie, E., & Mouton, J. (2007). The Practice of Social Research. Cape Town: Oxford University Press.Baker, J. P., & Ozaki, R. (2008). Pro-environmental Products: Marketing Influence on Consumer Purchase Decision. Journal of Consumer Marketing, 25(5), 281-293.Barber, Nelson, Taylor, David, C., Strick, & Sandy. (2009). Environmental Knowledge and Attitudes: Influencing the Purchase Decisions of Wine Consumers. International CHRIE Conference-Refereed Track, Paper 16.Baron, R. M., & Kenny, D. A. (1986). The Moderator-Mediator Variable Distinction in Social Psychological Research: Conceptual, Strategic, and Statistical Considerations. Journal of Personality and Social Psychology, 51(6), 1173.Belch, G. E., & Belch, M. A. (1995). Introduction to Advertising and Promotion: An Integrated Marketing Communications Perspective. London: Richard D. Irwin.Bryman, A., & Bell, E. (2007). Business Research Methods, 2nd Edition. Oxford: Oxford University Press.Bush, A. J., Martin, C. A., & Clark, P. W. (2001). The Effect of Role Model Influence on Adolescents' Materialism and Marketplace Knowledge. Journal of Marketing Theory and Practice, 9(4), 27-36.Chairy. (2012). Spirituality, Self Transcendence, and Green Purchase Intention in College Students. Procedia - Social and Behavioral Sciences, 57, 243-246.Chen, T. B., & Chai, L. T. (2010). Attitude towards the Environment and Green Products: Consumers’ Perspective. Management Science and Engineering Volume 4, 29-30.Cronbach, L. (1951). Coefficient Alpa and the Internal Structure of Tests. Psychomerika, 16, 297-334.Dafler, F. (2013, April 23). Memahami dan Mempelajari SmartPLS. Retrieved February 20, 2019, from Terindah: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDouglas, M. (. (2015, September 22). Sources of Data. Retrieved 3 3, 2019, from Online Tymology Dictionary: http://www.onlineetymologydictionary/dataD'Souza, C., Taghian, M. L., & Peretiatko. (2007). Green Decisions: Demographics and Consumer Understanding of Environmental Labels. International Journal of Consumer Studies, 31, 371-376.Duhan, D. F., Johnson, S. D., Wilcox, J. B., & Harrell, G. D. (1997). Influences on Consumer Use of Word of Mouth Recommendation Sources. Journal of the Academy of Mar-keting Science, 25(4), 283-295.Eze, U. C., & Ndubisi, N. O. (2013). Green Buyer Behaviour: Evidence from Asian Consumers. Journal of Asian and African Studies, Vol. 48 No. 4, 413-426.Finisterra do Paço, A. M., Raposo, M., & Mário , L. (2010). Green Consumerism: Perspectives, Sustainability, and Behavior. International Journal of Consumer Studies.Fryxall, G., & Lo, C. (2003). The Influence On Environmental Knowledge and Values on Managerial Behaviors on Behalf of The Environment: An Empirical Examination of Managers in China. Journal of Business Ethics, 45-59.Gary, P. S., & Bradnee , W. C. (1999). The Role of the World Trade Organization in Global Governance. . Tokyo: United Nations University Press.Ghozali, I. (2008). Structural Equation Modelling, Edisi II. Semarang: Universitas Diponegoro.Ghozali, I. (2012). Aplikasi Analisis Multivariate dengan IBM SPSS 20. Semarang: Universitas Diponegoro.Good, J. (2006). Internet Use and Environmental Attitudes: a Social Capital Approach. The Environmental Communication Yearbook, Vol. 3, 211-233.Han, H., Hsu, L., & Sheu, C. (2010). Application of the Theory of Planned Behavior to Green Hotel Choice: Testing the Effect of Environmental Friendly Activities. Tourism Management, 31, 325–334.Harris, S.M. . (2007). Does Sustainability Sell? Market Responses to Sustainability Certification. Management of Environmental Quality: An International Journal, pp. 50-60.Hasan, Z., & Ali, N. A. (2015). The Impact of Green Marketing Strategy on the Firm’s Performance in Malaysia. Procedia - Social and Behavioral Sciences, 172, 463-470.Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved from Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysis-with-lisrel-chapter-1/Hoch, S. J., & Banerji, S. (1993). When Do Private Labels Succeed? Sloan Management Review 34, 57–67.Irland, L. C. (1993). Wood Producers Face Green Marketing Era: Environmentally Sound Products. Wood Technology. 120 -134.Karatu, V. H., & Nik Mat, N. K. (2015). Predictors of Green Purchase Intention in Nigeria : The Mediating Role of Environmental Consciousnes. American Journal of Economic, 5(2), 291-302.Kong, W., Harun, A., Sulong, R. S., & Lily, J. (2014). The Influence of Consumers’ Perception of Green Products on Green Purchase Intention. International Journal of Asian Social Science Journal, 4(8), 924-939.Kothari, C. R. (1985). Research Methodology-Methods and Techniques, New. New Delhi: Wiley Eastern Limited.Kotler, Keller, & Philip. (2009). Marketing Management Analysis, Planning, Implementation. London: Pearson Education International, Prentice Hall.Laroche, M., Bergeron, J., & Barbaro, F. G. (2001). Targeting consumers who are willing to pay more for environmentally friendly products. Journal of Consumer Marketing, 18(6), 503-520.Laroche, M., Toffoli, R., Kim, C., & Muller, T. E. (1996). The Influence of Culture on Pro-Environmental Knowledge, Attitudes, and Behaviors: a Canadian Perspective. Corfman, K.P. and Lynch, J.G. (Eds), Advances in Consumer Research, Association for Consumer Research, Provo, UT, Vol. 23, 196-202.Lee, K. (2008). Making Environmental Communications Meaningful to Female Adolescents: a Study in Hong Kong. Science Communication, Vol. 30 No. 2, 147-176.Lee, K. (2010). The Green Purchase Behavior of Hong Kong Young Consumers: The Role of Peer Influence, Local Environmental Involvement, and Concrete Environmental Knowledge. Journal of International Consumer Marketing, Vol. 23 No. 1, 21-44.Lee, K. (2014). Predictors of Sustainable Consumption among Young Educated Consumers in Hong Kong. Journal of International Consumer Marketing, Vol. 26 No. 3, 217-238.Luchs, M. G., Naylor, R. W., Irwin, J. R., & Raghunathan, R. (2010). The Sustainability Liability: Potential Negative Effects of Ethicality on Product Preference. Journal of Marketing, 74, 18–31.McGuiness, J., Jones, A. P., & Cole, S. G. (1977). Attitudinal Correlates of Recycling Behavior. Journal of Applied Psychology, 62, 376-384.Mei, O. J., Ling, K. C., & Piew, T. H. (2012). The Antecedents of Green Purchase Intention among Malaysian Consumers. Asian Social Science, 248-263.Messick, S. (1995). Standards of Validity and the Validity of Standrads in Performance Assesment. Educational Measurement: Issues and Practice, 14(4), 5-8.Miller, K. E., & Layton, R. A. (2001). Fundamentals of marketing (4th Edition). Sydney: McGraw-Hill.Mohd Noor, M. N., Sreenivasan, J., & Ismail, H. (2013). Malaysian Consumers Attitude Towards Mobile Advertising, the Role of Permission and its Impact on Purchase Intention: A Structural Equation Modeling Approach . Asian Social Science, 9(5), 135-153.Mohr, L. A., Eroğlu, D., & Ellen, P. S. (1998). The Development and Testing of a Measure of Skepticism Toward Environmental Claims in Marketers’ Communications. Journal of Consumer Affairs, Vol. 32 No. 1, 30-55.Mostafa, M. M. (2006). Antecedents of Egyptian Consumers' Green Purchase Intention: A Hierarchical Multivariate Regression Model. Journal of International Consumer Marketing, 19, 97-126.Mostafa, M. M. (2009). Shades of Green: A Psychographic Segmentation of the Green Consumer in Kuwait Using Self-Organizing Maps. Expert Systems with Applications, 36(8),, 11030-11038.Nittala, R. (2014). Green Consumer Behaviour of The Educated Segment in India. Journal of International Consumer Marketing, Vol. 26 No. 2, 138-152.Nwankwo, Sonny, Hamelin, Nicolas, Khaled, & Meryem. (2014). Consumer Values, Motivation and Purchase Intention for Luxury Goods. Journal of Retailing and Consumer Services, 735-744.Ohman, N. (2011). Buying or Lying - The Role of Social Pressure and Temporal Disjunction of Intention Assess Mental and Behavior on The Predictive Ability of Good Intentions. Journal of Retailing and Consumer Service, 18, 194 – 199.Oskamp, S., Harrington, M. J., Edwards, T. C., Sherwood, D. L., Okuda, S. M., & Swanson, D. C. (1991). Factors Influencing Household Recycling Behavior. Environmental Behavior, 23, 494–519.Othman, Jamal, Jeff, B., & Russell, B. (2004). Environmental Management and Resources Management Options: A Choice Modelling Experience in Malaysia. Environment and Development Economics, 9, 803-24.Peter, J. P., & Olson, J. C. (2013). Consumer Behavior and Strategic Marketing. New York: McGraw-Hill/Irwin.Rahbar, E., & Wahid, N.A. . (2011). Investigation of Green Marketing Tools’ Effect on Consumers Purchase Behavior. Business Strategy Series, Vol. 12 No. 2, 73-83.Rahbar, E., & Wahid, N. A. (2010). Ethno-Cultural Differences and Consumer Understanding of Eco-Labels: An Empirical Study in Malaysia. Journal of Sustainable Development, 255-262.Rezai, G., Mohamed , Z., & Shamsudin, M. N. (2011). Malaysian Consumer's Perspection towards Purchasing Organically Produces Vegetable. Proceedings of the 2nd International Conference on Business and Economics Research.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlRoberts, J. A. (1996). Green consumers in the 1990s: Profile and implications for advertising. Journal of Business Research, 217-231.Rogers, E. M. (2003). Diffusion of Innovations. New York: Free Press.Schultz, P. W., & Zeleny, L. C. (2000). Promoting Environmentalism. The Journal of Social Issues, 56, 443-457.Schwepker, C. H., & Cornwell, T. B. (1991). An examination of ecologically concerned consumers and their intention to purchase ecologically packaged products. Journal of Public Policy and Marketing, 10, 77-101.Shrum, L. J., Lowrey, T. M., & McCarty, J. (1994). Recycling as a Mark-Sting Problem: A Framework for Strategy Development. Psychology and Marketing 11 , 393-416.Solomon, M. R. (2011). Consumer Behavior: Buying, Having and Being. Upper Saddle River: Pearson.Straub, D. W. (1989). Validating Instruments in MIS Research. MIS Quarterly, 13(2), 147-169.Straub, D., Boudreau, M. C., & Gefen , D. (2004). Validation Guidelines for IS Positivist Research. Commncation of the Association for Information System, 13, 380-427.Sugiyono. (2008). Statistik Untuk Penelitian. Bandung: Alfabeta.The Jakarta Post. (2015, November 6). Indonesia Second Biggest Marine Pollutant, After China. Retrieved February 4, 2019, from The Jakarta Post: https://www.thejakartapost.com/news/2015/11/06/indonesia-second-biggest-marine-pollutant-after-china.htmlVinzi, V., W. W., H., & Wang, H. (2010). Handbook of Partial Least Squares: Concepts, Methods, and Apllication. New York: Springer Publishing.Welman, C., Kruger, F., & Mitchell, B. (2009). Research Methodology. 3rd Edition. Cape Town: Oxford University Press.Wikipedia. (2016). Wikipedia. Retrieved from Discriminant Validity: https://en.wikipedia.org/wiki/Discriminant_validityYoung, W., Hwang, K., McDonald, S., & Oates, C. J. (2010). Sustainable consumption: Green Consumer Behaviour When Purchasing Products. Sustainable Development, 18(1), 20-31.Zhu, B. (2013). The Impact of Green Advertising on Consumer Purchase Intention of Green Products. World Review of Business Research, 3(3), 72-80.